Cutting stability and optimization of process parameters for the large-pitch screw high-feed turning. (October 2019) - Fu, Xiangfu; Li, Zhe; Zheng, Minli; Wang, Xiurui; Li, Junwei
In this study, the machining characteristics of the large-pitch screw in high-feed turning are initially analyzed, and a dynamic model for the screw subjected to moving forces is proposed to study the chatter, which has been taken into consideration "quasi-regeneration effect" of the machined surface and the actual machining path. Then, a stability model of the lobes between the amount of feed and spindle speed in the turning screw finishing stage is achieved, taking into consideration deformation of the workpiece and the tool, on the basis of the vibration equation of the workpiece and the dynamic equation of the tool, and is experimentally verified as well. The dynamics model, and stability domain provide a basis upon which multiobjective process parameter optimization method including the amount of feed and spindle speed can be put forward during high-feed turning process. Experiments are likewise performed and the results show that no chatter occurs, verifying the optimization of machining process parameters for large-pitch turning. Meanwhile, it should be noted that the surface quality and shape accuracy of the machined surface are equivalent to the high-feed turning process.